The Analysis Study of Surgical Management of Hernia Inguinalis in Children : A Pediatric Surgery Systematic Review - Yosie Yulanda Putra; Ririn Azhari (International Medical Journal Corp. Ltd, 2024)
Background: Inguinal hernia is a type of abdominal wall hernia, accounting for 7% of surgical consultations and 12% of total surgical procedures globally. Inguinal hernia can occur at any age, and premature infants have the highest incidence. Surgical treatment for inguinal hernia in children is necessary to avoid severe complications. Methods: This systematic review followed the PRISMA 2020 guidelines, focusing on full-text articles published in English between 2014 and 2024. Editorial and review articles without DOI were removed to ensure only high-quality sources were used. A comprehensive literature search process was performed through leading databases such as ScienceDirect, PubMed, and SagePub to identify studies relevant to this research topic. Results: An initial database search revealed more than 1000 publications relevant to this topic. After a thorough three-stage screening process, eight studies were selected based on pre-defined inclusion criteria and deemed eligible for further in-depth analysis. Each selected study underwent a thorough critical appraisal to ensure its quality and relevance, thus providing a solid foundation for a comprehensive study on the role of surgical management in the management of pediatric inguinal hernia. Conclusion: Laparoscopy is a minimally invasive procedure that requires specialized equipment that may not be available at all centers. Laparoscopic repair is gaining popularity due to its advantages over open surgery. Laparoscopic surgery is a viable option, but it has not shown significant advantages in terms of recurrence or short-term outcomes when compared to open surgery.